Are physicians aware enough of patient radiation protection? Results from a survey among physicians of Pavia District– Italy - Francesca Campanella; Laura Rossi; Elio Giroletti; Piero Micheletti; Fabio Buzzi; Simona Villani (BMC Health Services Research, 2017)
Abstract Background Radiological practices are the first anthropic sources of ionizing radiation exposure of the population. However, a review of recent publications underlines inadequate doctors’ knowledge about doses imparted in medical practices and about patient protection that might explain unnecessary radiological prescriptions. We investigated the knowledge of the physicians of Pavia District (Italy) on the risk of radiation exposure. Methods A cross sectional study was performed involving the Medical Association of Pavia District. Data were collected with a self-administered questionnaire, available on-line with private login and password. Results Four hundred nineteen physicians fulfilled the questionnaire; 48% of participants reported training about radiation protection. The average percentage of correct answers on the knowledge on ionizing radiation was 62.29%, with a significantly higher result between radiologist. Around 5 and 13% of the responders do not know that, respectively, ultrasonography and magnetic resonance do not expose patients to ionizing radiations. Only 5% of the physicians properly identified the cancer risk rate associated to abdomen computed tomography. Conclusions The findings show a quite good level of the general knowledge about ionizing radiations, higher that reported in literature. Nevertheless, we believe the usefulness of training on the risk linked to radiation exposure in medicine for physicians employed in every area.